Gender, Subsistence, Change, and Resilience in Quinhagak’s Present and Past - Sloan, Anna (Études Inuit Studies, 2019)
Like many other Alaska Native communities, the Yup’ik people of Quinhagak follow a subsistence lifestyle that is multi-faceted, socially embedded, and specifically tailored to the land and water on which it is practiced. This paper provides a synthesis of Quinhagak residents’ perspectives on subsistence in both the present and the past, as documented in original interviews and in the literature, with a focus on how gendered social identities are enacted through these traditions. The Nunalleq site presents a unique opportunity to examine the time depth of local subsistence lifeways and their social iterations, as well as how these were affected by changing landscapes and climate—all realities of contemporary Quinhagak life, just as they were for the ancestors at Nunalleq. The interrelation of subsistence and sociality has implications for how we understand Yup’ik resiliency and survivance in the face of such changes.